The drives towards controlling plastic consumption:A study in UiTM Kampus Seremban / Nur Asyikin Soberi ... [et al.] - Soberi, Nur Asyikin; Yusuf, Intan Nurulyusmida; Mohd Shazali, Nurliyana; Ahmad, Nasyrah (2021)
Plastic waste is a significant environmental issue for decades as it poses a major threat to the ecosystem, especially for the marines like sea turtles and whales. Plastics refer to polymers (either they are made synthetically or from natural resources like tar, shells, and cellulose) and consist of a mixture of materials that go through a heating process to retain their shapes (History Science Institute, 2021). The combination of polymers with other unique things such as low density, low electrical conductivity, transparency, and toughness has given room for plastics to be widely used in many sectors throughout the world (Rodriguez, 2020). According to WWF Australia (2021), plastics take a long time to be decomposed, depends on their types and usage. For instance, normal plastic bags will be fully decayed after 20 years, and a kid's toothbrush will perish after 500 years. Malaysia had been stated as the biggest plastic consumer by the WWF in its report, whereby an individual in Malaysia generally produced 16.8 kg/person compared to Thailand (15.5 kg/person) per year (Reuters, 2020). In addition, the culture of Malaysians that like to 'tapao' (take away) foods and drinks had accelerated the usage of plastics in Malaysia and this had caused the existed landfills to overflow with low-value plastic packaging and sachets (Lee, 2021). In short, this phenomenon leads to further analysis on plastic consumption behaviour, particularly among the current tertiary students who are more exposed to the 'tapao' culture and possess some ideas about the effects of plastic consumption (thanks to the lectures and wider coverage and information on the sites regarding the matter).